Spatial and Temporal Distribution of Phyllophaga spp. Infesting Bermudagrass Stands in Oklahoma. Issue 1 (19th October 2017) - Graf, N.; Rebek, E.; Royer, T.; Walker, N.
Abstract : Larvae of Phyllophaga spp. (Coleoptera: Scarabaeidae) are important direct and indirect turfgrass pests in the southern United States. Confirming the presence of these larvae is an important integrated pest management practice in turf production systems and determines the need for treatment. However, several different species (e.g., P. crinita, P. submucida, and P. crassissima ) are known to occur within the same turfgrass stand, and each species has a different oviposition period. The objective of this study was to determine the spatial and temporal distribution of Phyllophaga spp. in intensely managed bermudagrass. During spring through summer of 2009, larvae were collected after harvesting bermudagrass turf from two sod farms in Oklahoma. The location of each grub was determined using global positioning system tracking. Identification of larvae was based on polymerase chain reaction amplification and sequencing of the cytochrome c oxidase I gene. Species spatial and temporal distribution patterns were analyzed by detrended correspondence analysis using CANOCO 5.04. Seven species of Phyllophaga were collected, and each study site contained at least one species that was not found at the other. Detrended correspondence analysis resulted in low β diversity values. Beta diversity reflects how far apart species are in the gradient of species composition. The low β diversity scores obtained in this study show that different species of Phyllophaga were present in no recognizable pattern of temporal or spatial distribution.